Development of an Interactive Global Surgery Course for Interdisciplinary Learners - Tamara N. Fitzgerald; Nyagetuba J. K. Muma; John A. Gallis; Grey Reavis; Alvan Ukachukwu; Emily R. Smith; Osondu Ogbuoji; Henry E. Rice (Ubiquity Press, 2021)
Introduction: Global surgical care is increasingly recognized in the global health agenda and requires multidisciplinary engagement. Despite high interest among medical students, residents and other learners, many surgical faculty and health experts remain uniformed about global surgical care. Methods: We have operated an interdisciplinary graduate-level course in Global Surgical Care based on didactics and interactive group learning. Students completed a pre- and post-course survey regarding their learning experiences and results were analyzed using the Wilcoxon signed-rank test. Results: Fourteen students completed the pre-course survey, and 11 completed the post-course survey. Eleven students (79%) were enrolled in a Master's degree program in global health, with eight students (57%) planning to attend medical school. The median ranking of surgery on the global health agenda was fifth at the beginning of the course and third at the conclusion (p = 0.11). Non-infectious disease priorities tended to stay the same or increase in rank from pre- to post-course. Infectious disease priorities tended to decrease in rank (HIV/AIDS, p = 0.07; malaria, p = 0.02; neglected infectious disease, p = 0.3). Students reported that their understanding of global health (p = 0.03), global surgery (p = 0.001) and challenges faced by the underserved (p = 0.03) improved during the course. When asked if surgery was an indispensable part of healthcare, before the course 64% of students strongly agreed, while after the course 91% of students strongly agreed (p = 0.3). Students reported that the interactive nature of the course strengthened their skills in collaborative problem-solving. Conclusions: We describe an interdisciplinary global surgery course that integrates didactics with team-based projects. Students appeared to learn core topics and held a different view of global surgery after the course. Similar courses in global surgery can educate clinicians and other stakeholders about strategies for building healthy surgical systems worldwide.